URGENSI ISLAMISASI SAINS - Salminawati Salminawati; Muhammad Azhar (Universitas Islam Negeri Sumatera Utara Medan, 2021)
While science is trying to find solutions to human problems in this modern era, scholars are trying with all their might to find alternative methods of science and new technology, which can provide solutions to the problems of mankind in this modern era. Along with the rapid progress of science and technology in the West, religious values slowly began to shift and contradict science. Currently, Muslims only rely on science discovered and innovated by western scientists, causing Islamic civilization to be increasingly marginalized in the midst of the progress of Western countries that adopt a secular system. Seeing the decline of science in the Islamic world, Muslim scholars, especially those in the world of education, gave rise to the idea of